2021
DOI: 10.1007/s11804-021-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Effects of Periodic Gust Flow on the Wake Structure of Ventilated Supercavities

Abstract: A computational model is established to investigate the effects of a periodic gust flow on the wake structure of ventilated supercavities. The effectiveness of the computational model is validated by comparing with available experimental data. Benefited from this numerical model, the vertical velocity characteristics in the entire flow field can be easily monitored and analyzed under the action of a gust generator; further, the unsteady evolution of the flow parameters of the closed region of the supercavity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Yang et al studied the effect of heating a hydrofoil surface on cavitation and found that transient cavitation occurs on the surface of the heated hydrofoil, and with the increase in temperature, the transient cavitation will become open-type cavitation . Wang et al studied the influence of periodic gust flow on the cavitation shape at the tail of ventilated supercavitation . Zhan et al studied the influence of lateral flow on supercavitation and concluded that the cavity morphology is symmetrical in the absence of lateral flow and asymmetrical in the presence of lateral flow, with the cavity morphology increasing with the velocity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al studied the effect of heating a hydrofoil surface on cavitation and found that transient cavitation occurs on the surface of the heated hydrofoil, and with the increase in temperature, the transient cavitation will become open-type cavitation . Wang et al studied the influence of periodic gust flow on the cavitation shape at the tail of ventilated supercavitation . Zhan et al studied the influence of lateral flow on supercavitation and concluded that the cavity morphology is symmetrical in the absence of lateral flow and asymmetrical in the presence of lateral flow, with the cavity morphology increasing with the velocity .…”
Section: Introductionmentioning
confidence: 99%
“… 16 Wang et al studied the influence of periodic gust flow on the cavitation shape at the tail of ventilated supercavitation. 17 Zhan et al studied the influence of lateral flow on supercavitation and concluded that the cavity morphology is symmetrical in the absence of lateral flow and asymmetrical in the presence of lateral flow, with the cavity morphology increasing with the velocity. 18 Fan et al studied the change in supercavitation when the projectile passes through different density regions and found that the diameter contraction of the projectile occurs through different density regions and in different locations and is related to the density degree.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, other flow characteristics had also been studied through numerical simulation methods. Wang et al (2021) established a computational model to investigate the effects of a periodic gust flow on the wake structure of ventilated supercavity. The conclusions demonstrated that the behavior of ventilated supercavity against unsteady incoming flow was more stable than the vapor cavity.…”
mentioning
confidence: 99%